Effect of rainwater oxidants on As volatilization in the soil-rice system. (February 2022) - Lin, Xiaoyang; Li, Huashou; Li, Yichun
Abstract: Rainwater contains multiple oxidants, such as hydrogen peroxide (H2 O2 ) and perchlorate (ClO4 − ). The aim of the study was to investigate the rainwater of trace H2 O2 and ClO4 − affected on the arsenic (As) methylation and volatilization in the rice paddy of As contamination (arsenite (As(III)) and roxarsone (Rox)). Heavy rainfall monitoring and simulation experiments were applied in this study. The result showed that the H2 O2 and ClO4 − of heavy rainfall in 2017 was 5.3–51.6 μmol/L and ND - 6.1 μg/L respectively. Because of the differences in chemical properties, H2 O2 and ClO4 − affected As methylation and volatilization of paddy soil in different ways. H2 O2 performed a temporary effect on As volatilization, which was mainly in the 1st-hour and restored to the controls condition finally. However, ClO4 − showed a persistent inhibition on As volatilization which decreased 32 %–69 % in the whole test. In general, the trend of volatilization was following the order: CK ≈ H2 O2 > ClO4 − . The oxidants (H2 O2 and ClO4 − ) also could decrease As(III) in 37 %–44 % and increased As(V) in 24 %–272 %. In addition, planting rice in As contamination soil could enhance As volatilization by 36 %–334 %. These suggested that planting wetland plants on As-contaminated soil probably become a potential way to increase As volatilization. Graphical abstract: Image 1 Highlights: H2 O2 could temporarily effect on As volatilization in soil. ClO4 − could persistently inhibit on As volatilization in soil. Planting rice could enhance As volatilization in soil.